The Armenians of Musa Dagh, 1915-1939 - Çiçek, Kemal, 1965- (Lanham, Maryland)
ix, 119 sayfa
Keywords: “This book examines the narratives surrounding the Musa Daghian rebellion and its consequence in present-day Hatay, Turkey. Analyzing both Armenian and Ottoman primary sources, Kemal Çiçek examines the Armenian resistance, flight to the Musa Mountain, and eventual rescue by the Allies' navy.“ --